2002
DOI: 10.1046/j.1440-1827.2002.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of chaperone protein expression in presenilin mutant neurons in response to glutamate excitotoxicity

Abstract: Mutations in the presenilin-1 (PS1) gene underlie the most common form of familial dementia of the Alzheimer type (DAT). We demonstrated previously that the expression of PS1 with a M146V mutation in transgenic mice potentiates glutamate toxicity to neurons, due to an altered calcium homeostasis. Here, using a subtractive cDNA library approach, we report the identification of several genes, the altered expression of which may be associated with this unique PS1-related vulnerability to glutamate. The identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Cam activity has previously been implicated in regulating the stability and proteolysis of other integral membrane proteins [54]. Interestingly, others have shown that calmodulin RNA levels can be impacted by FAD- Psn expression [55]. We have been unable to detect any effect of loss of a single Cam allele on the FAD-presenilin protein levels (Figure S1).…”
Section: Discussionmentioning
confidence: 70%
“…Cam activity has previously been implicated in regulating the stability and proteolysis of other integral membrane proteins [54]. Interestingly, others have shown that calmodulin RNA levels can be impacted by FAD- Psn expression [55]. We have been unable to detect any effect of loss of a single Cam allele on the FAD-presenilin protein levels (Figure S1).…”
Section: Discussionmentioning
confidence: 70%
“…56,57 As with up-regulated genes, several observations overlap with the known differences in other neurodegenerative diseases.…”
Section: Scgt1/gt1 Hypothalamic Cell Gene Regulationmentioning
confidence: 90%
“…Thus far, neuronal NPM1 has been investigated in two independent studies in the context of excitotoxicity, a process that leads to the necrotic death of neurons. These studies showed that NPM1 mRNA is decreased in glutamate-treated cortical cultures from PS1 M146V mutant transgenic mice (39) and that its protein is down-regulated in degenerating neurons of the rat hippocampal CA1 region, as well as primary neuronal cultures following kainic acid treatment (13). We report, however, that NPM1 expression is increased in both the R6/2 transgenic and 3-NP chemical mouse models of Huntington's disease.…”
Section: Discussionmentioning
confidence: 57%